2017
DOI: 10.1007/s00383-017-4120-5
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in access and outcomes for emergency neonatal surgery: intestinal atresia in Kampala, Uganda

Abstract: Level IV, Case series with no comparison group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…These findings, however, were not in agreement with the report by Cairo et al, wherein many neonates with intestinal atresia presented after day 7. 18 HD, on the other hand, was a major cause of obstruction in other reports, but in our study the incidence was low. 4 11 A study conducted by Saha et al showed a 35.3% incidence of HD, higher than that of atresia, whereas in other related studies the incidence was almost equal, with HD leading over atresia.…”
Section: Etiological Spectrumcontrasting
confidence: 71%
See 1 more Smart Citation
“…These findings, however, were not in agreement with the report by Cairo et al, wherein many neonates with intestinal atresia presented after day 7. 18 HD, on the other hand, was a major cause of obstruction in other reports, but in our study the incidence was low. 4 11 A study conducted by Saha et al showed a 35.3% incidence of HD, higher than that of atresia, whereas in other related studies the incidence was almost equal, with HD leading over atresia.…”
Section: Etiological Spectrumcontrasting
confidence: 71%
“…16 A report by Cairo et al indicated a mortality rate of 43% among neonates with intestinal atresia. 18 These figures are quite high compared to the findings in Europe, where a mortality is less than 15% among neonates with obstruction. 3 9 With such glaring disparities in mortality, there is a huge need to understand the high rate and more specially to identify the predictors, which are not well elucidated in our setting.…”
Section: Open Accessmentioning
confidence: 76%
“…A newborn is a baby born within 28 days from umbilical cord ligation. Neonatal intestinal obstruction refers to the obstruction of the normal delivery of the contents of the intestinal cavity of the newborn to cause partial or complete failure to pass, resulting in systemic physiological dysfunction [10]. e incidence rate is higher than 1%, which is the main cause of neonatal acute abdomen and one of the important causes of perinatal infant death [11].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical management for ileal atresia reported by Hiller et al is in favour of primary resection and anastomosis than secondary anastomosis (14). This neonate was managed by constructing a double-barrel ileostomy owing to the fact there was gross peritoneal contamination by meconium and bowel oedema mitigating the risk of the anastomotic leak (15). Consequently, the neonate deteriorated at home following poor, inadequate breast-feeding by the mother and eventually died in the hospital upon readmission from severe acute malnutrition and hypothermia six weeks later.…”
Section: Discussionmentioning
confidence: 99%